Meta-Analysis of the Effects of Stress and Anxiety on Alcohol Consumption Behavior in Early Adults - Windya Kartika Paramita; Argyo Demartoto; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Consumption of alcoholic beverages is a risk factor for health problems globally. The consumption of alcoholic beverages is very influential on the effect of calmness in people who have anxiety and stress disorders. The effect occurs because alcohol is classified as a psychoactive substance that affects nerves in the brain with the effect of dependence on the dose consumed. This study aims to assess the effect size of stress and anxiety on increased alcohol consumption behavior in early adulthood using a meta-analysis of primary studies conducted by the previous authors. Subjects and Method: This study was a meta-analysis with the following PICO, population: Early adults (18-25 years). Intervention: Stress and Anxiety. Comparison: no stress and no anxiety. Result: Increased Alcoholic Beverages Consumption Behavior. 9 The articles used in this study were obtained from three databases namely Google Scholar, PubMed, and Scopus. The keywords for searching for articles were stress AND (Anxiety OR nervousness OR discomfort) AND (